Ensuring Fair Business Practices and Consumer Rights: The Role and Impact of Indonesia's Consumer Dispute Settlement Agency - Dhaniswara K. Harjono; Hulman Panjaitan; Moermahadi Soerjadjanegara; Hendra Susanto; Abu Hena Mostofa Kamal; Suwarno Suwarno (Unissula, 2024)
This research examines the role and impact of Indonesia's Consumer Dispute Settlement Agency (BPSK) in promoting fair business practices and protecting consumer rights in a changing economic environment. It focuses on Consumer Protection Law No. 8 of 1999 and uses a legal research method to analyze how effective BPSK is at resolving disputes between consumers and businesses. The findings show that, while BPSK offers alternative dispute resolution methods like mediation and conciliation, it struggles with issues such as interference from the courts, lack of independence, and limited authority. The Indonesian Supreme Court often overturns BPSK's decisions, which lowers public trust in the agency. Additionally, BPSK's reactive approach to complaints and procedural delays limit its ability to actively protect consumer rights. This study suggests that structural reforms are needed to give BPSK more independence and power, including clearer rules for resolving disputes and the ability to impose penalties for violations. By addressing these challenges, Indonesia can strengthen BPSK's role in protecting consumer rights and ensuring fair business practices, leading to a better legal framework for consumer protection.